Old South Meeting House, ca. 1890 - Unknown (Tufts Archival Research Center, 2005)
Elevated view east-northeast of the Old South Meeting House, located on Washington Street at the northeast corner of Washington and Milk Streets. The facade of the church faces west-northwest towards Washington Street, while its south-southwest elevation faces Milk Street. Other buildings are included in the photograph. Several pedestrians are visible on the sidewalk along Washington Street. Built by Joshua Blanchard, 1729 9 x 6 7/8 Photographs